Potential terrestrial influence on transparent exopolymer particle concentrations in boreal freshwaters. (15th May 2019) - Attermeyer, Katrin; Andersson, Sara; Catalán, Núria; Einarsdottir, Karolina; Groeneveld, Marloes; Székely, Anna J.; Tranvik, Lars J.
Abstract: Transparent exopolymer particles (TEP) are ubiquitous in aquatic ecosystems and contribute, for example, to sedimentation of organic matter in oceans and freshwaters. Earlier studies indicate that the formation of TEP is related to the in situ activity of phytoplankton or bacteria. However, terrestrial sources of TEP and TEP precursors are usually not considered. We investigated TEP concentration and its driving factors in boreal freshwaters, hypothesizing that TEP and TEP precursors can enter freshwaters via terrestrial inputs. In a field survey, we measured TEP concentrations and other environmental factors across 30 aquatic ecosystems in Sweden. In a mesocosm experiment, we further investigated TEP dynamics over time after manipulating terrestrial organic matter input and light conditions. The TEP concentrations in boreal freshwaters ranged from 83 to 4940 μ g Gum Xanthan equivalent L −1, which is comparable to other studies in freshwaters. The carbon fraction in TEP in the sampled boreal freshwaters is much higher than the phytoplanktonic carbon, in contrast to previous studies in northern temperate and Mediterranean regions. Boreal TEP concentrations were mostly related to particulate organic carbon, dissolved organic carbon, and optical indices of terrestrial influence but less influenced by bacterial abundance, bacterial production, and chlorophyll a . Hence, our results do not support a major role of the phytoplankton community or aquatic bacteria on TEP concentrations and dynamics. This suggests a strong external control of TEP concentrations in boreal freshwaters, which can in turn affect particle dynamics and sedimentation in the recipient aquatic ecosystem.